A qualitative exploration of the discharge process and factors predisposing to readmissions to the intensive care unit - Uchenna R. Ofoma; Yue Dong; Ognjen Gajic; Brian W. Pickering (BMC, 2018)
Abstract Background Quantitative studies have demonstrated several factors predictive of readmissions to intensive care. Clinical decision tools, derived from these factors have failed to reduce readmission rates. The purpose of this study was to qualitatively explore the experiences and perceptions of physicians and nurses to gain more insight into intensive care readmissions. Methods Semi-structured interviews of intensive care unit (ICU) and general medicine care providers explored work routines, understanding and perceptions of the discharge process, and readmissions to intensive care. Participants included ten providers from the ICU setting, including nurses (n = 5), consultant intensivists (n = 2), critical care fellows (n = 3) and 9 providers from the general medical setting, nurses (n = 4), consulting physicians (n = 2) and senior resident physicians (n = 3). Principles of grounded theory were used to analyze the interview transcripts. Results Nine factors within four broad themes were identified: (1) patient factors - severity-of-illness and undefined goals of care; (2) process factors - communication, transitions of care; (3) provider factors - discharge decision-making, provider experience and comfort level; (4) organizational factors - resource constraints, institutional policies. Conclusions Severe illness predisposes ICU patients to readmission, especially when goals of care were not adequately addressed. Communication, premature discharge, and other factors, mostly unrelated to the patient were also perceived by physicians and nurses to be associated with readmissions to intensive care. Quality improvement efforts that focus on modifying or improving aspects of non-patient factors may improve outcomes for patients at risk of ICU readmission.